2017
DOI: 10.2527/tas2017.0063
|View full text |Cite
|
Sign up to set email alerts
|

National Beef Quality Audit–2016: Transportation, mobility, live cattle, and carcass assessments of targeted producer-related characteristics that affect value of market cows and bulls, their carcasses, and associated by-products1

Abstract: The National Beef Quality Audit–2016 marks the fourth iteration in a series assessing the quality of live beef and dairy cows and bulls and their carcass counterparts. The objective was to determine the incidence of producer-related defects, and report cattle and carcass traits associated with producer management. Conducted from March through December of 2016, trailers (n = 154), live animals (n = 5,470), hide-on carcasses (n = 5,278), and hide-off hot carcasses (n = 5,510) were surveyed in 18 commercial packi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 18 publications
2
25
0
Order By: Relevance
“…Often these cows are in a compromised condition and may deteriorate quickly. Several benchmarking studies, described in detail below, have characterized the condition of cull cows arriving at slaughter plants, noting conditions with grave welfare implications for the cow [4,14,15]. We argue that some of these culling decisions should actually be euthanasia decisions.…”
Section: How Timely Euthanasia and Culling Decisions Are Intertwinedmentioning
confidence: 99%
See 2 more Smart Citations
“…Often these cows are in a compromised condition and may deteriorate quickly. Several benchmarking studies, described in detail below, have characterized the condition of cull cows arriving at slaughter plants, noting conditions with grave welfare implications for the cow [4,14,15]. We argue that some of these culling decisions should actually be euthanasia decisions.…”
Section: How Timely Euthanasia and Culling Decisions Are Intertwinedmentioning
confidence: 99%
“…We argue that some of these culling decisions should actually be euthanasia decisions. Although the majority of culled cattle arriving at slaughter facilities are in adequate condition and are fit for transport [14], not all culled cattle should be sold into the supply chain. If they are suffering and not fit for transport, producers should elect to euthanize these animals, rather than sell them.…”
Section: How Timely Euthanasia and Culling Decisions Are Intertwinedmentioning
confidence: 99%
See 1 more Smart Citation
“…Bruises not only impact overall carcass value but also raise concerns about cattle welfare and, therefore, bruising has received considerable interest within the cattle industry. The 2016 National Beef Quality Audit (NBQA) reported a bruise prevalence of 38.8%, 64.1%, and 42.9% for finished steer and heifer, cow, and bull carcasses, respectively ( Eastwood et al, 2017 ; Harris et al, 2017 ). Similarly, in a large commercial study exploring risk factors associated with bruising in the United States, Lee et al (2017) reported that 68.2% of cattle observed were bruised.…”
Section: Introductionmentioning
confidence: 99%
“…Industry reports have estimated that bruising costs the cattle industry millions of dollars in lost carcass value annually ( Henderson, 2016 ). Although data from the past several NBQAs have indicated general reductions in bruise prevalence, there are still opportunities for improvement ( Eastwood et al, 2017 ; Harris et al, 2017 ). Additionally, the NBQA reported that critical and extreme bruises made up 2.4% and 6.3% of bruises in finished steers and heifers and cull cows and bulls, respectively ( Eastwood et al, 2017 ; Harris et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%